High prevalence of fragmented QRS on electrocardiography in Japanese patients with diabetes irrespective of metabolic syndrome. Issue 9 (2nd March 2021) - Yagi, Kunimasa; Nagata, Yoshiki; Yamagami, Takashi; Chujo, Daisuke; Kamigishi, Miki; Yokoyama‐Nakagawa, Maki; Shikata, Masataka; Enkaku, Asako; Takikawa‐Nishida, Akiko; Honoki, Hisae; Fujisaka, Shiho; Origasa, Hideki; et al.
Abstract: Aims/Introduction: Fragmented QRS (fQRS) on electrocardiography is a marker of myocardial fibrosis and myocardial scar formation. This study aimed to clarify the relationship of fQRS with diabetes mellitus and metabolic syndrome (MetS) in Japanese patients. Materials and Methods: Approximately 702 individuals who had a routine health checkup at the Hokuriku Health Service Association (Toyama, Japan) in October 2014 were enrolled and categorized into one of the following four groups based on MetS and diabetes mellitus status: with diabetes mellitus (+) MetS+ (164 participants); diabetes mellitus+ without MetS (Mets−; 103 participants); diabetes mellitus− MetS+ (133 participants); and diabetes mellitus− MetS− (302 participants). fQRS was assessed using the results of electrocardiography. Results: The prevalence of fQRS was statistically higher in patients with diabetes mellitus+ MetS+ (37%) and diabetes mellitus+ MetS− (35%), than those with diabetes mellitus− MetS+ (14%) or diabetes mellitus− MetS− (10%; P < 0.0001). Significant differences were observed between the fQRS(+) and fQRS(–) groups for age, sex, waist circumference, heart rate, hypertension, hemoglobin A1c, total cholesterol, MetS and diabetes mellitus. The area under the receiver operating characteristic curve for traditional risk factors and diabetes mellitus was 0.72 ( P = 0.0007, 95% confidence interval 0.67–0.76), and for traditional risk factors and MetS it was 0.67 ( P = 0.28, 95% confidence interval 0.62–0.72). Patients with diabetes mellitus had more than threefold higher likelihood of showing fQRS (odds ratio 3.41; 95% confidence interval 2.25–5.22; P < 0.0001) compared with the reference group without diabetes mellitus, after adjusting for age, sex, dyslipidemia, hypertension and waist circumference. Conclusions: fQRS was observed more frequently in diabetes mellitus patients than in MetS and control individuals. Diabetes mellitus was the most significant determinant for fQRS among MetS and other traditional metabolic risk factors. Abstract : Fragmented QRS was observed more frequently in patients with diabetes mellitus than in metabolic syndrome and control individuals. Diabetes mellitus was the most significant determinant for fragmented QRS among metabolic syndrome and other traditional metabolic risk factors.